Allograft inflammatory factor-1 (AIF-1) is crucial for the survival and pro-inflammatory activity of macrophages - Zhen Yang; David W. Ho; Chi Keung Marco Lau; Chi Tat Lam; Ching Tung Lum; Ronnie T.P. Poon; Sheung Tat Fan (2005)
Our previous studies revealed that macrophages played an important role in linking injury, inflammatory and immune response in small-for-size liver transplantation. However, the molecular basis that promoted macrophage activation was not clear. In the present study, we explored the potential role of allograft inflammatory factor-1 (AIF-1) in mediating the survival and pro-inflammatory activity of macrophages in a macrophage cell line. First, the expression of AIF-1 was investigated with the stimulation of pro-inflammatory cytokines and anti-inflammatory treatment. Second, the level of inducible nitric oxide synthase (iNOS) and the survival and migration activity of macrophages were determined with the alterations of AIF-1 expression. Finally, a potential molecule that regulated AIF-1 expression was identified by the proteomic approach. The macrophage cell line expressed a certain level of endogenous AIF-1, which could be enhanced by pro-inflammatory cytokines IL-1β or tumor necrosis factor-α and suppressed by anti-inflammatory drug sodium salicylate. AIF-1 augmentation induced by AIF-1/PCDNA3.1(+) transfection enhanced the levels of iNOS and monocyte chemoattractant protein-1, and promoted the cell migration. On the other hand, suppression of AIF-1 expression by AIF-1/short interference RNA (siRNA) inhibited iNOS production, induced macrophage cell apoptosis and blocked the cell migration. Using two-dimensional electrophoresis, a disintegrin and metalloproteinase domain 3 (ADAM3) was identified after AIF-1/siRNA transfection. Transfection of ADAM3/PCDNA3.1(+) up-regulated the expression of AIF-1 and iNOS, whereas suppression of ADAM3 expression down-regulated AIF-1 and iNOS expression. In conclusion, AIF-1 played an important role in the survival and pro-inflammatory activity of macrophages, and ADAM3 might be an upstream molecule that regulated AIF-1 expression.